The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1128/iai.63.10.3864-3870.1995
|View full text |Cite
|
Sign up to set email alerts
|

Generation of interleukin-8 from human monocytes in response to Trichomonas vaginalis stimulation

Abstract: Neutrophils are the predominant inflammatory cells found in the vaginal discharges of patients with Trichomonas vaginalis infection. We have investigated the possible role of interleukin-8 (IL-8) in the inflammatory response elicited by T. vaginalis infection. This study has shown that T. vaginalis induces blood monocytes to produce large amounts of bioactive IL-8, mainly by membrane components of T. vaginalis (MTV). Monocyte-derived IL-8 induced by MTV was dose and time dependent. The peak level of IL-8 was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Controversial studies have been published concerning cytokines profile that may be induced in response to T. vaginalis infection. Some previous studies in vitro revealed that exposure to T. vaginalis stimulated IL-8 secretion in human monocytes, [21] neutrophils, [22] and vaginal epithelial cells. [23] It was further demonstrated that the cytokines IL-2 and IFN-γ were secreted by murine lymphocytes infected with T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…Controversial studies have been published concerning cytokines profile that may be induced in response to T. vaginalis infection. Some previous studies in vitro revealed that exposure to T. vaginalis stimulated IL-8 secretion in human monocytes, [21] neutrophils, [22] and vaginal epithelial cells. [23] It was further demonstrated that the cytokines IL-2 and IFN-γ were secreted by murine lymphocytes infected with T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine Interleukin-8 (IL-8, CXCL8) is a member of the CXC chemokine family that plays a number of important roles in immunity including activation and attraction of neutrophils [ 1 , 2 ]. In vitro, IL-8 is produced by neutrophils, macrophages, monocytes and epithelial cells when exposed to either microbial products derived from commensal bacteria or organisms that cause sexually transmitted infections (STI) [ 3 5 ]. IL-8 levels in lower genital tract secretions are increased in women with STIs [ 5 7 ] and also increased in response to non-STI alterations in lower genital tract microbiota [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While overall immune responses during trichomonosis are largely unknown, high levels of interleukin‐8 (IL‐8) and leukotreine B4 (LTB4) have been found in the vaginal secretions from symptomatic patients with trichomonosis (Shaio et al ., 1994; 1995; Shaio and Lin, 1995). There are also reports of IL‐8 produced in response to T. vaginalis stimulation by human neutrophils (Ryu et al ., 2004) and human monocytes (Shaio et al ., 1995). Further, in vitro studies have revealed that IL‐8 production is regulated through NF‐κB and MAP kinase signalling pathways.…”
Section: Introductionmentioning
confidence: 99%